Reproductive decisions after neonatal screening identifies cystic fibrosis. Issue 2 (1st March 2000) - Dudding, Tracy; Wilcken, Bridget; Burgess, Bronwyn; Hambly, Judy; Turner, Gillian
Abstract : AIMS: To document the reproductive choices made by women in New South Wales, Australia, after neonatal screening has identified cystic fibrosis (CF). METHODS: A sample of women attending cystic fibrosis clinics in New South Wales who had a child (or children) diagnosed by neonatal screening between 1981 and 1996 were interviewed. RESULTS: Two thirds of the women chose to avoid having another child with CF. The uptake of prenatal diagnosis was 66% in women who had a subsequent pregnancy; of these 69% terminated or would have terminated an affected fetus. Fifty nine per cent of the women who decided against a further pregnancy made this decision in order to avoid having another child with CF. CONCLUSIONS: These data show that having a child with CF influenced subsequent reproductive choices. In addition to the medical advantages of an early diagnosis offered by neonatal screening, this also allows informed future reproductive decisions.